Recent advances in highly integrated energy conversion and storage system. Issue 2 (9th March 2022) - Shao, Changxiang; Zhao, Yang; Qu, Liangti
Abstract: The vigorous development in the field of energy conversion and storage devices directly contributes to the full utilization and convenient use of clean energy. However, some drawbacks of independent energy conversion and storage devices, including unstable, insufficient energy output and dependence on external power supply, are difficult to overcome by self‐optimization, thus, hindering their further development and direct application. Coincidentally, the combination of above two devices can solve these problems, which conforms to their intrinsic needs for development. At the same time, the pursuit of portability and miniaturization also promotes the development of the power system toward a highly integrated direction. Therefore, we introduce several integration modes of energy conversion and storage systems, with emphasis on all‐in‐one power system, possessing the highest integration in this review. From the aspect of device configuration, working mechanisms and their performances, the all‐in‐one power systems based on different energy sources (e.g., mechanical, solar, thermal, and chemical energy) are discussed and analyzed. Finally, the design strategies are summarized and the potential development directions in the future are proposed. This review aims to provide a comprehensive overview of highly integrated energy conversion and storage system, and seeks to point out the opportunities and orientations of future research in this field. Abstract : The integration of energy conversion and storage devices is the inevitable development trend of the next‐generation intelligent power system, which attracts extensive attention. In this review, we introduce four combination modes of integrated systems, and put emphasis on the latest progress in all‐in‐one power systems. Through the discussion and analysis of the device configurations, working mechanisms, and performances of the all‐in‐one devices based on different energy sources, the design strategies are summarized. This review aims to provide a comprehensive overview of highly integrated energy conversion and storage system, and seeks to point out the opportunities for future investigation.